The Everyday in a Time of Transformation: Exploring a Single South African Lifeworld after 20 Years of Democracy - Kotze, P. Conrad; Coetzee, Jan K. (Qualitative Sociology Review, 2017)
Transformation has come to be a defining characteristic of contemporary societies, while it has rarely been studied in a way that gives acknowledgement to both its societal effects and the experience thereof by the individual. This article discusses a recent study that attempts to do just that. The everyday life of a South African is explored within the context of changes that can be linked, more or less directly, to those that have characterized South Africa as a state since the end of apartheid in 1994. The study strives to avoid the pitfalls associated with either an empirical or solely constructivist appreciation of this phenomenon, but rather represents an integral onto-epistemological framework for the practice of sociological research. The illustrated framework is argued to facilitate an analysis of social reality that encompasses all aspects thereof, from the objectively given to the intersubjectively constructed and subjectively constituted. While not requiring extensive development on the theoretical or methodological level, the possibility of carrying out such an integral study is highlighted as being comfortably within the capabilities of sociology as a discipline. While the article sheds light on the experience of transformation, it is also intended to contribute to the contemporary debate surrounding the current “ontological turn” within the social sciences.